STUDENT TEAM ACHIEVEMENT DIVISION (STAD) LEARNING MODEL TO IMPROVE ELEMENTARY SCHOOL STUDENTS' CIVICS LEARNING OUTCOMES - Mutia Erliana (Teaching and General Education Studies, 2025)
This study aims to improve the Civics Education (PKN) learning outcomes of fourth-grade students at SDN 28 Lubuklinggau through the implementation of the Student Team Achievement Division (STAD) learning model. The background of this research is the low learning outcomes and student engagement in Civics Education, which require innovative strategies to foster active participation and deeper understanding of national values. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of the study were 24 fourth-grade students. Data were collected using tests, observations, interviews, and documentation. In the first cycle, the average student score was 57.08 with 9 out of 24 students (37.50%) achieving the Minimum Completeness Criteria (KKM). After improvements were made, the second cycle showed a significant increase with an average score of 77.5 and 20 students (83.33%) meeting the KKM. These findings suggest that the STAD model is effective in improving both student activity and learning outcomes in Civics Education, particularly in understanding the meaning of Pancasila values in daily life. The use of cooperative strategies helped students become more engaged and motivated during the learning process. In conclusion, the STAD model can be considered an effective approach to enhance learning outcomes and foster collaborative skills among elementary students. Future research is recommended to examine its application in other subjects and grade levels to explore broader impacts.